Spatial Order of Peripheral Areas in Aspects of Partition - Podciborski, Tomasz; Kil, Jacek (Regional Barometer. Analyses & Prognoses, 2011)
This study presents a method to assess the effects of arrangements resulting from the preliminary project of property subdivision performed during the property subdivision survey on the spatial order status in non-urbanized areas. The paper also demonstrates practical applications of the method developed.